1963
DOI: 10.1542/peds.32.2.298
|View full text |Cite
|
Sign up to set email alerts
|

Child-Rearing Practices in a Low Socioeconomic Group

Abstract: Our findings support the view that there are characteristics in child-rearing practices which are related to class status, and that these differences become more pronounced with the extremes of class. In this sample of low-class mothers interviewed when tile child was 2½ years of age, we found some maternal rejection of the child, coldness, and physical punishment. There was lack of restrictiveness in regard to toilet training and training for manners. At 5 years there was much restrictiveness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1965
1965
1991
1991

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In a gratuitous confirmation of recent psychotherapeutic findings, infant theorists and researchers hold that regnant characteristics of the interacting adult's mode of response include accurate understanding, sensitive responsiveness, and facilitative accommodation in carrying forward the infant's behavior toward its natural effects (Ainsworth, Bell, & Stayton, 1972;Ainsworth & Wittig, 1969;Bettleheim, 1967;Bowlby, 1969;Lambie & Weikart, 1970;Rheingold, 1961;Walters & Park, 1965;. Studies of depriving home environments (Wortis, 1963) and institutions (Provence & Lipton, 1961;Yarrow, 1961) provide soft indirect evidence of the importance of this ingredient. Furthermore, research indicates that the adult should provide immediate responses (Ainsworth, 1967;Ainsworth, Bell & Stayton, 1972;Cairns, 1966;Gewirtz, 1969;Lewis & Goldberg, 1965;Watson, 1966Watson, , 1967Yarrow, Rubenstein, Pedersen, & Jankowski, 1972) to a wide spectrum of infant behaviors (Yarrow, 1973).…”
Section: The Research Foundationmentioning
confidence: 99%
“…In a gratuitous confirmation of recent psychotherapeutic findings, infant theorists and researchers hold that regnant characteristics of the interacting adult's mode of response include accurate understanding, sensitive responsiveness, and facilitative accommodation in carrying forward the infant's behavior toward its natural effects (Ainsworth, Bell, & Stayton, 1972;Ainsworth & Wittig, 1969;Bettleheim, 1967;Bowlby, 1969;Lambie & Weikart, 1970;Rheingold, 1961;Walters & Park, 1965;. Studies of depriving home environments (Wortis, 1963) and institutions (Provence & Lipton, 1961;Yarrow, 1961) provide soft indirect evidence of the importance of this ingredient. Furthermore, research indicates that the adult should provide immediate responses (Ainsworth, 1967;Ainsworth, Bell & Stayton, 1972;Cairns, 1966;Gewirtz, 1969;Lewis & Goldberg, 1965;Watson, 1966Watson, , 1967Yarrow, Rubenstein, Pedersen, & Jankowski, 1972) to a wide spectrum of infant behaviors (Yarrow, 1973).…”
Section: The Research Foundationmentioning
confidence: 99%
“…Differences between the child-rearing practices of lower-class and middle-class parents have been documented. 39 From inter views with parents of children at ages two-and-a-half and five, it was found that child-rearing patterns in lower-class families were characterized by less posi tive affect and more restrictiveness and punitiveness than middle-class families.…”
Section: Since the Discovery That Children From Lower Socioeconomic (...mentioning
confidence: 99%
“…The subjects were drawn from a sam ple studied in the course of an investi gation of the development of premature infants in relation to certain complica tions of the neonatal period. The selec tion of the sample and the objectives of the study have been described; several previous reports have been made on these subjects.2, a, 4,6, 7, 19,20,21 The subjects were ( 1 ) premature, single-birth Negro infants (weighing up to 2100 grams at birth) who were ad-mitted to the Kings County Hospital Premature Nursery from October, 1956, to June, 1959, and (2) a small number of Negro term infants born in the same place. Kings County is a municipal hos pital which serves the medically indigent in a densely populated area with a very high prematurity rate.12 Premature chil dren born to white and Puerto Rican mothers also were followed.…”
mentioning
confidence: 99%